A Pilot Study of Obesity Management: Contributions of Cognitive-Behavioral Group Therapy to Stress, Anxiety, and Emotional Eating - Paiva Porto, Andressa (2025)
Objetive. Cognitive-Behavioral Group Therapy (CBGT) is a group approach that assesses the interconnections between thoughts, emotions, and behaviors in a group setting. This study aimed to assess the feasibility and preliminary effectiveness of a CBGT protocol focused on emotion regulation, in reducing emotional reactivity and its potential impact on components of emotion-driven eating behaviors. Method. Twenty participants underwent an 8-week intervention, with half receiving psychoeducational intervention and the other half receiving CBGT with a focus on emotional regulation. We used questionnaires to assess anxiety and eating behavior, and we measured psychophysiological changes through cortisol levels and heart rate variability. Results. After six weeks, the CBGT group had lower scores for emotional and uncontrolled eating, along with an increase in parasympathetic modulation and a decrease in cortisol levels. These results suggest that CBGT may hold potential for improving emotional regulation and reducing emotion-based eating behavior; however, further research is needed to confirm its effectiveness.